Graphical Password Using Captcha - Y.Chandra Sekhar Reddy; M.Venkateswara Rao; M. Kameswara Rao; C.V. Phaneendra Kumar; A. Anil Sai (Institute of Advanced Engineering and Science, 2016)
In this 21st century one of the main issue to tackle was Cyber Security attack. We have numerous authentication processes like two key factor passwords, graphical passwords and many other. Text based passwords are prone to many attacks like dictionary attacks. In this paper, we have implemented a new authentication method namely; a family of graphical passwords built on Captcha technology. As graphical password addresses many security problems like online guessing attacks, relay attacks etc. Captcha is used to distinguish humans and bots. So, we use images with captcha’s as one of the authentication step along with normal alpha-numeric password. It also overcome the problems of pass points in graphical password systems.